Pathological Analysis of Ocular Lesions in a Murine Model of Sjögren’s Syndrome - Ushio, Aya (Int J Mol Sci, 2017)
Sjögren’s syndrome (SS) is a systemic autoimmune disease characterized by severe inflammation of exocrine glands such as the salivary and lacrimal glands. When it affects the lacrimal glands, many patients experience keratoconjunctivitis due to severely dry eyes. This study investigated the pathological and immunological characteristics of ocular lesions in a mouse model of SS. Corneal epithelial injury and hyperplasia were confirmed pathologically. The number of conjunctival mucin-producing goblet cells was significantly decreased in the SS model mice compared with control mice. Expression levels of transforming growth factor (TGF)-β, interleukin (IL)-6, tumor necrosis factor (TNF)-α, and C-X-C motif chemokine (CXCL) 12 were significantly higher in the corneal epithelium of the SS model mice than in control mice. Inflammatory lesions were observed in the Harderian, intraorbital, and extraorbital lacrimal glands in the SS model mice, suggesting that the ocular glands were targeted by an autoimmune response. The lacrimal glands of the SS model mice were infiltrated by cluster of differentiation (CD)4(+) T cells. Real-time reverse transcription-polymerase chain reaction (RT-PCR) revealed significantly increased mRNA expression of TNF-α, TGF-β, CXCL9, and lysozyme in the extraorbital lacrimal glands of the SS model mice compared with control mice. These results add to the understanding of the complex pathogenesis of SS and may facilitate development of new therapeutic strategies.